Peran Komunikasi Internal Dalam Mengurangi Fenomena Quiet Quitting Pada Generasi Z Di Tempat Kerja: The Role of Internal Communication in Reducing the Phenomenon of Quiet Quitting Among Generation Z in the Workplace - Suparto Putri, Lyshell; Sunjaya, Natalia Angel; Lee, Shandy Aulia; Ningtyas, Dinda Zahra; Chandhika, Jessica (Innovative: Journal Of Social Science Research, 2025)
This study focuses on the role of internal communication in reducing the phenomenon of quiet quitting among Generation Z in the workplace. The research sample consists of Generation Z individuals who have been working for at least one year, including both males and females. The sampling method used is simple random sampling, where respondents are selected randomly without considering strata. The research instruments consist of questionnaires, and the measurement tools used are Quiet Quitting and Internal Communication scales. This study specifically examines the role of internal communication in mitigating quiet quitting among Generation Z employees. The findings of this study are: (1) males exhibit higher levels of quiet quitting compared to females, although this difference is not statistically significant, and (2) no significant relationship was found between internal communication and quiet quitting. This indicates that internal communication does not directly correlate with lower levels of quiet quitting. These findings suggest that quiet quitting is influenced by various factors beyond internal communication, such as leadership style, work pressure, and job satisfaction. Therefore, further research is needed to identify other factors that contribute to the emergence of this phenomenon.